CONCEPTUAL FRAMEWORK ON PSYCHOLOGICAL CONTRACT - Manisha Goswami, Dr. Supriya Jain (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Over the past two decades, research work on Psychological contract has been flourishing quite rapidly in the domain of Human Resource Management. However, the concept is in to academic existence from 1960s, as a distinction from a formal written employment agreement which only defines shared duties and responsibilities, a psychological contract reflects the common values, expectations and informal obligations between an employer and an employee. This paper discusses some of the key concerns of the psychological contract in context of current scenario. To develop awareness and perceptive, this literature reassess the importance of an alternate perspective, focused on an analytical and extensive literature analysis, to study the psychological contract. From this, the researchers analyse the Psychological Contract concept as exemplified in current researches and asserts that it signifies, in its current context, an explicitly tailored for a specific managerial understanding of contemporary work and employment.